2003
DOI: 10.1046/j.1526-4610.2003.03094.x
|View full text |Cite
|
Sign up to set email alerts
|

Naratriptan in the Preventive Treatment of Refractory Chronic Migraine: A Review of 27 Cases

Abstract: Naratriptan may have a role in the preventive treatment of intractable chronic migraine. Prospective, controlled studies should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…There are as yet no universally reliable prophylactic drugs for migraine. Drugs to treat acute attacks have already been developed, but they do not prevent attacks although naratriptan has been recommended for this purpose 223 . Of all of the classes of preventative drugs, few can be said to have been a great deal different from placebo.…”
Section: Preventing Migrainementioning
confidence: 99%
“…There are as yet no universally reliable prophylactic drugs for migraine. Drugs to treat acute attacks have already been developed, but they do not prevent attacks although naratriptan has been recommended for this purpose 223 . Of all of the classes of preventative drugs, few can be said to have been a great deal different from placebo.…”
Section: Preventing Migrainementioning
confidence: 99%
“…Furthermore, patients were not allowed to start new acute treatments during the study. So, although symptomatic treatment of headache pain may have prophylactic effects, 36 any such effect resulting from acute medication use would have already been present at the time of enrollment into the study. Furthermore, during the course of the study the use of acute medications decreased.…”
Section: Commentsmentioning
confidence: 99%
“…24 A retrospective study found a reduction of 36.5% in headache frequency at 2 months in patients using daily naratriptan. 26 We found that levetiracetam may be an effective drug in the prevention of TM. For the ITT population, headache frequency decreased 34.9%, the number of days with moderate or severe headache pain decreased by 42.2%, and disability scores decreased significantly (both, P _< 0.01).…”
Section: Discussionmentioning
confidence: 84%